2011
DOI: 10.1007/s10897-011-9392-7
|View full text |Cite
|
Sign up to set email alerts
|

Iona College Community Centered Family Health History Project: Lessons Learned from Student Focus Groups

Abstract: The Community Centered Family Health History project was initiated to create accessible family health history tools produced by and for the community. The project goal was to promote increased community engagement in health education by encouraging conversations among family members that would translate knowledge of family health history into healthy lifestyle choices. As one of seven community partners, Iona College participated in customizing and beta-testing the Does It Run in the Family? toolkit. Twenty-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Students discussed this assignment as an opportunity for communication with family members and taking a more proactive role in their health [6]. Students' reflections related to social cognitive theory, where students learned through their research experiences by observing others' actions during family interviews and subsequent health interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students discussed this assignment as an opportunity for communication with family members and taking a more proactive role in their health [6]. Students' reflections related to social cognitive theory, where students learned through their research experiences by observing others' actions during family interviews and subsequent health interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Other FHH research targeting students and their families in a three-month intervention reported improved ability to openly communicate about family health issues [6]. Many students initiated conversations with healthcare providers and improved their physical activity and nutrition.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We also did not attempt to follow up with participants to learn whether they really did share FHH information with relatives or providers. Previous work in this area has shown that the practice of sharing FHH information with relatives and providers increases overall levels of communication and trust, makes nonparticipant relatives more willing to discuss health issues with their providers, and increases overall knowledge of risk factors associated with chronic diseases within the family [ 34 , 66 , 67 ], but those studies were done in a general population sample, and it is not clear whether they would be generalizable to the low-income and minority populations reached in this pilot program. More work is needed to determine whether a FHH educational program such as this one truly influences participant behavior around collecting and sharing FHH data.…”
Section: Discussionmentioning
confidence: 99%
“…The Genetic Alliance recommended that future interventions follow this two-pronged approach of customization and integration as a successful method for promoting FHH collection in underserved communities. The Genetic Alliance’s evaluation of this effort, however, focused primarily on the usability of the toolkit and did not assess whether the groups continued to offer the intervention after the initial project period [ 18 , 31 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%